Averting War in Northeast Asia: A Proposal - Mel Gurtov (Japan Focus)
While the United States and South Korea consider whether or not to accept North Korea's call for an "unconditional" return to the Six Party Talks (6PT) or China's call for multilateral negotiations, Northeast Asia is sliding in the direction of deepening conflict that could lead to war. China-Japan relations, which had been warming since the departure of Koizumi Junichiro, and especially since the victory of the Democratic Party of Japan in 2008, are again in a deep freeze over disputed territory. One consequence is a reorientation of Japan's defense strategy southward, in the direction of the Senkakus (Diaoyutai). Washington is encouraging that shift, as well as closer military cooperation between Japan and South Korea. North-South Korea relations are very tense as the result of the Cheonan incident, the North's artillery barrage against a small South Korean island, and revelations of a modern North Korean uranium enrichment plant-all coming in the wake of the Lee Myung Bak administration's almost complete reversal of his predecessors' engagement policies. And China-US relations are increasingly contentious, going beyond the longstanding differences over currency valuation and human rights to include a host of security matters. Even though China-Taiwan relations have improved, U.S. naval activity in the Pacific has picked up, with a number of exercises conducted alone and with allies leading some Chinese analysts to conclude that containment is again prominent on the U.S. policy agenda. And both China and the United States are beefing up their weapons capabilities relevant to the Taiwan Strait.A bipolar lineup, reminiscent of the Cold War, is shaping up, with China, Russia, and North Korea on one side, the United States, Japan, South Korea, Taiwan, and India on the other-with each side competing for the affections of the ten Southeast Asian countries grouped under ASEAN. Despite substantial economic ties between all these countries-even between the two Koreas, until Lee Myung Bak suspended trade with the North last spring-their political and strategic divisions are wide and deep.President Hu Jintao's January 19, 2011 visit to Washington provides the occasion to attempt a diplomatic breakthrough. The most critical need of countries in Northeast Asia is an institution for crisis prevention, crisis management, and other security-promoting purposes-what might be called a Northeast Asia Security Dialogue Mechanism (NEASDM). It would be an outgrowth of the Six Party Talks, where all the parties twice agreed (in 2005 and 2007) to create such a mechanism. This article outlines the nature of such a dialogue mechanism.